Inclusão para alunos do campo com deficiência na escola Cristo Redentor no município de Abaetetuba-PA - SILVA, Keila de Jesus Ferreira da (2019)
The present work was carried out through a bibliographical and field research and had the subject to discuss the "Inclusion for students of the field with deficiency in the school Cristo Redentor in the municipality of Abaetetuba -Pa". With the general aim of knowing and analyzing how teachers work in the classroom the teaching and learning process with the disabled students, in the 6th grade class, Elementary School, the Cristo Redentor school and as specific objectives to analyze how the process is carried out education and learning with students with disabilities, to reflect the problems related to the inclusion of students with disabilities at the Cristo Redentor School, and to discuss the challenges faced by the students in the countryside to access education in a regular and urban school. In order to reach the proposed objective, a qualitative approach was chosen, as it provided the widening of the debate around the natural conjuncture of the research and the enrichment of the description of the obtained data. A field research was also carried out, in order to know the teacher‟s conception about the inclusive policy of the researched municipality. On the theoretical contribution, we present some concepts necessary to the understanding of what is special education, inclusion and education in the field and on how are the practices of teaching learning with the subjects attended by special education. As results achieved, we noticed that although the school points out advances in conceptions aimed at inclusion for students with SEN, there are still several conflicts that teachers face in the concretization of the ideas of the education of these subjects for a better effectiveness of teaching learning.